Awareness of Chronic Kidney Disease among Tamil Nadu Population- A Cross-sectional Study - R Chandan Bala; M Jayabharathy; S Sheba Yesu Priya; S Ramya (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Chronic kidney failure in India and around the world is a significant health problem. The most effective and affordable treatment may require screening for early detection,intervention and prevention. Public awareness is a key determinant to overcome the burden of Chronic Kidney Disease(CKD). However, there is a lack of information on CKD among South Indian people. Aim: To assess the awareness and knowledge of CKD among the South Indian population. Materials and Methods: A questionnaire-based cross-sectional study was conducted through an online form; the questions were generally based on the physiological role of kidney and awareness questions related to CKD. The sample size was 500 participants, of age >18 years and snowball sampling method was implemented. Among the study population, 68 participants had a family history of CKD and they were excluded. The data were analysed through Pearson Chi-Square test. Results: The mean knowledge score was 13 (SD±5.0), with values ranging from 0 to 22. The mean age of the population was 47.80±8.5 years. Multiple regression on demographic data and knowledge yielded statistically negligible results.The study population included 432 participants and the result showed the realms that most responded incorrectly were physiology of kidney, CKD symptoms, risk factors and the domain of testing and diagnosis. Conclusion: The participants had ample knowledge of the risk factors, signs and symptoms of CKD and insufficient knowledge of the physiological function of the kidney and the diagnosis of CKD. Therefore, efforts are necessary to create awareness and educate people about the early detection and prevention of CKD.